2004
DOI: 10.1007/s00347-003-0940-x
|View full text |Cite
|
Sign up to set email alerts
|

Tiefe Sklerektomie mit Hyaluronatimplantat vs. Trabekulektomie

Abstract: As a more aggressive IOP-lowering procedure (intended filtration, use of antimetabolites) deep sclerectomy proved to be as effective as trabeculectomy. Nevertheless, the advantages of the more difficult surgical procedure concerning visual acuity, complications and surgical interventions were lost postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Trabeculectomy significantly reduced IOP in all eyes in our study, similar to other reported data [16,17,18]. Suture removal significantly improved the complete success rate at 12 months from 65 to 94%.…”
Section: Discussionsupporting
confidence: 82%
“…Trabeculectomy significantly reduced IOP in all eyes in our study, similar to other reported data [16,17,18]. Suture removal significantly improved the complete success rate at 12 months from 65 to 94%.…”
Section: Discussionsupporting
confidence: 82%
“…A total of 24 articles were excluded, including 9 full reports [16,17,18,19,20,21,22,23,24], and 15 meeting abstracts (see Appendix 1). Out of them, 17 randomized controlled trials were included in the present meta-analysis, 14 published in full form [25,26,27,28,29,30,31,32,33,34,35,36,37,38] and 3 published in abstract form (see Appendix 2). The flowchart of the studies included in our analysis is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…If the ruptured regions of the juxtacanalicular tissue and canal heal with time, surgery may fail in eyes that did not develop filtration blebs. This problem is soon to be seen in the increasing failure rates of nonpenetrating filtering surgery with time [27, 35]. In an attempt to minimize this healing response, some surgeons have used MMC as an adjunct, and the favorable effect of MMC has been shown [39,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors described success rates for similar techniques as standard trabeculectomy in Caucasian patients with open-angle glaucoma [7, 8, 12, 13,28,29,30,31]. Others showed an inferior success rate (defined as an IOP lower than 21 mm Hg without medication) than with standard trabeculectomy [10, 11, 26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…The results are controversial: some studies showed deep sclerectomy as superior [1, 4], others as similar or inferior [7,8,9,10,11,12,13] to standard trabeculectomy in the treatment of open-angle glaucoma. All authors described fewer early postoperative complications using a non-penetrating technique [4,6,7,8, 12, 14]. …”
Section: Introductionmentioning
confidence: 99%